Why internal migration threatens local health equity more than global flight - Gulnaz Fatima Siddiqui; Shahid Akhtar Siddiqui (Tropical Doctor, 2026)
Global policy debates remain heavily preoccupied with the international migration of healthcare workers to wealthy nations, largely overlooking a more pressing issue. For frontline communities in low- and middle-income countries, the internal migration of medical specialists from rural public facilities to urban private sectors poses a far more insidious threat to local health equity. By draining crucial skill sets from those areas where the burden of disease is at its worst to the richest urban centers, this subterranean drain creates even greater imbalances in terms of healthcare within the nation than does flight to other countries.